IMPLEMENTASI KEBIJAKAN PROGRAM PENGELOLAAN SAMPAH DI KOTA BANDUNG PROVINSI JAWA BARAT - Saputra, Ginanjar Wira; Santosa, Pandji; Adiwisastra, Jossy (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
The waste management problem in Bandung City has reached a critical level, marked by daily waste volume exceeding the capacity of the Sarimukti Final Disposal Site (TPA). This condition has prompted the Bandung City Government to implement a series of policies aimed at reducing waste at its source. This study aims to analyze the implementation of waste management program policies in Bandung City, focusing on the "Kang Pisman" (Reduce, Separate, Utilize) program using the analytical framework of the George C. Edwards III Policy Implementation Model which includes four key variables: communication, resources, disposition, and bureaucratic structure. The method used is a qualitative approach with literature studies and document analysis to collect relevant secondary data. This methodological limitation implies that the analysis focuses more on regulatory and structural aspects, while the dimensions of community behavior and implementation dynamics at the field level are examined through policy documents and official reports, rather than direct observation. The results of the study indicate that although implementation is supported by a strong legal basis such as Regional Regulation No. 9 of 2018 and various mayoral regulations, their effectiveness is hampered by unequal communication down to the household level, limited infrastructure and budget, and varying dispositions of implementers and the community. The theoretical contribution of this research lies in the systematic application of the Edwards III Model in the context of decentralized urban waste management in Indonesia, which enriches the public policy implementation literature by identifying that the success of innovative, community-based programs requires the simultaneous alignment of all four implementation variables. The practical implications are the need to strengthen locality-based communication, more proportional resource allocation, and the establishment of cross-sectoral coordination mechanisms to improve the effectiveness of sustainable waste management programs in Indonesian metropolitan cities.